2022
DOI: 10.1039/d2ma00331g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of van der Waals stacking in CdS monolayer on enhancing the hydrogen production efficiency of SiH monolayer

Abstract: Photocatalytic water splitting for hydrogen generation utilizing a highly efficient type II van der Waals (vdW) heterostructure is a novel class of materials with highly tunable bandgap energy and band...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…The green isosurfaces depict weak interactions due to van der Waals dispersion forces, which seek to explain the fluctuation in charges resulting in a non-specific and non-directional attraction. 59 The red isosurfaces, on the other hand, depict strong interactions primarily due to steric repulsion, though they influence the conformation and reactivity of ions and molecules. Nevertheless, the scatter maps establish the appearance of peaks in extremely very negative zones of the eigenvalue ( λ 2 ) depicted by the blue color on the horizontal axis, implying that the complexes (S@MoS 2 -QD-NH 3 , Si@MoS 2 -QD-NH 3 , P@MoS 2 -QD-NH 3 , N@MoS 2 -QD-NH 3 , and B@MoS 2 -QD-NH 3 ) must have very strong attractive intermolecular interactions, confirming the existence of hydrogen bonds which stabilize the interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The green isosurfaces depict weak interactions due to van der Waals dispersion forces, which seek to explain the fluctuation in charges resulting in a non-specific and non-directional attraction. 59 The red isosurfaces, on the other hand, depict strong interactions primarily due to steric repulsion, though they influence the conformation and reactivity of ions and molecules. Nevertheless, the scatter maps establish the appearance of peaks in extremely very negative zones of the eigenvalue ( λ 2 ) depicted by the blue color on the horizontal axis, implying that the complexes (S@MoS 2 -QD-NH 3 , Si@MoS 2 -QD-NH 3 , P@MoS 2 -QD-NH 3 , N@MoS 2 -QD-NH 3 , and B@MoS 2 -QD-NH 3 ) must have very strong attractive intermolecular interactions, confirming the existence of hydrogen bonds which stabilize the interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated no signicant variation in the bond length of these three structures, and the interlayer distances are approximately 3.1 Å. The calculated binding energies E b are −23.082, −22.959 and −22.887 meV Å −2 for stacking I, II, and III patterns, respectively, which are lower than PtSe 2 /GaN, PtSe 2 / Arsenene, and etc., [48][49][50][51][52][53] conrming that PtSe 2 /Hf 2 CO 2 bilayer forms a stable vdW heterostructure. In addition, the band gaps of stacking I to III are 0.965, 0.964, and 0.957 eV respectively, calculated by the PBE method, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…51,53 Furthermore, the values of the binding energy are consistent with that in the CdS/SiH heterostructure. 42 In addition, the negative sign of the binding energy indicates that the GR/SiH heterostructure is energetically stable and it can be easily synthesized in an experiment. Furthermore, to check the mechanical stability against mechanical deformation of the GR/SiH heterostructure, we calculate its elastic constants C ij .…”
Section: Resultsmentioning
confidence: 99%
“…Han et al 41 reported that the combination between PtSe 2 and SiH materials to form a PtSe 2 /SiH heterostructure enhances the photocatalytic efficiency. Opoku et al 42 showed that the hydrogen production efficiency of the SiH monolayer can be improved when it was stacked on the CdS monolayer.…”
Section: Introductionmentioning
confidence: 99%